The Determinants Factors of Islamic Financial Inclusion in West Java: A Comparison Between Generation Z and Millennials - Haryadi, Amarila Indi (Journal of Consumer Studies and Applied Marketing, 2023)
Islamic finance is one of the fastest-expanding global financial systems, and it predicted that Islamic finance has promising future asset growth. As a country with the largest Muslim population, Indonesia has great potential in the Islamic economy and finance sector. The rise of Islamic finance in the world's financial system and Indonesia's huge potential have attracted the attention of the Indonesian government, which wants to make Indonesia a leader in the world's Islamic economy. West Java was chosen as a pilot province for other regions in developing Islamic finance. More than half of West Java's population comprises Generation Z and Millennials. These two generations will play important roles in financial institutions in the next decade and will dominate Indonesia in 2045. The main purpose of this study is to explore the determinants of Islamic financial inclusion of Generation Z and Millennials in West Java and compare them. The data from 616 respondents was collected and analyzed using PLS-SEM. It found that Generation Z and Millennials have differences in how much each factor affects them. The difference between them is that religiosity has a stronger influence on Millennials than on Generation Z, and social influence has a stronger influence on Generation Z than on Millennials. Overall, this study concludes that, consecutively, Islamic financial literacy, social influence, and religiosity influence Islamic financial inclusion among Generation Z and Millennials in West Java.